An Investigation of Challenges in Enterprise Resource Planning (ERP) Implementation: The Case of Public Sector in Malaysia - Dahlia Fernandez; Zaini Zaino; Hawa Ahmad (International Journal of Supply Chain Management, 2018)
The implementation of enterprise resource planning (ERP) system to surge the performance has induced various organizations towards its adoption. Even though the government may perhaps strive for enhancements from ERP adoption, however, the organizations may experience adverse effects. The aim of this study is to investigate the challenges in implementing the ERP system on public sector organizations. This study was conducted using questionnaires survey with 52 local authorities in Malaysia which have implemented the system. It is found that that the main challenge to implement ERP in public sector organization is due to the complexity of existing working structure (i.e. protocols, bureaucracy, etc.) in meeting ERP requirements. It is followed by the difficulties in adapting to the change brought by this system where its change the way people work, and lack of experience and appropriate skills in implementing this complex system.